2022
DOI: 10.3390/jcdd9090299
|View full text |Cite
|
Sign up to set email alerts
|

Post-Partum Depression Lactating Rat Model for Evaluating Ketamine’s Safety as a Pharmacotherapeutic Treatment: Roles in Cardiac and Urinary Function

Abstract: Depression is one of the world’s most common and mentally disabling illnesses. Post-partum depression is a subtype of depression that affects one in seven women worldwide. Successful pharmacological treatment must consider the consequences for both, since the mother–child bond is fundamental for the well-being of both mother and infant as well as the general development of the newborn. Changes in maternal physiology and/or behavior can significantly influence the development of breastfed infants. Ketamine has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Fukushima et al 25 demonstrated ketamine's safety in cardiovascular and urinary systems through a study involving catecholamine and indoleamine detection in rat cardiac muscles (Table 5).…”
Section: Ketaminementioning
confidence: 99%
“…Fukushima et al 25 demonstrated ketamine's safety in cardiovascular and urinary systems through a study involving catecholamine and indoleamine detection in rat cardiac muscles (Table 5).…”
Section: Ketaminementioning
confidence: 99%
“…). Another study showed that postnatal ketamine exposure prevented depression-like behaviour in maternally separated rat pups (Fukushima et al 2022). While early ndings in offspring are optimistic, rodent timing does not perfectly translate to human neurodevelopment, so further research is essential to ensure ketamine safety.…”
mentioning
confidence: 99%